Rethinking Masdar and The Line Megaprojects: The Interplay of Economic, Social, Political, and Spatial Dimensions - Mohamad Kashef (Land)
This study critically examines the rapid proliferation of megaprojects across the Arab region, with a focus on the Gulf Cooperation Council (GCC) countries, where large-scale developments are strategically deployed to reshape global economic influence and enhance geopolitical positioning. Megaprojects, characterized by their vast scale, substantial financial investment, and long-term impact, remain a subject of intense academic debate. While much of the literature questions their economic viability, citing frequent cost overruns and misalignment with localized urban priorities, megaprojects continue to emerge worldwide. Governments and developers promote megaprojects as catalysts for foreign investment, tourism growth, and enhancing the global stature of host countries and regions. Beyond financial and economic imperatives, megaprojects are fundamentally shaped by socio-spatial, socio-political, and capital accumulation dynamics, each playing a critical role in their justification and implementation. These interconnected forces influence the prioritization of large-scale developments, often reinforcing their persistence as dominant urban and infrastructural strategies despite well-documented uncertainties and risks. The study employs a comparative case study approach to analyze two high-profile megaprojects: Masdar City in Abu Dhabi and The Line in NEOM, Saudi Arabia. By examining their underlying motivations, political, social, and economic dynamics, and projected success factors, the study aims to provide an evidence-based assessment of the forces driving these large-scale developments and their potential for completion and long-term viability. This study contributes to the ongoing discourse on megaproject development by offering a nuanced, evidence-based analysis of the socio-political and economic forces shaping large-scale urban initiatives in the Arab region. By critically evaluating the motivations and viability of Masdar City and The Line, this research provides valuable insights that can inform future scholarly inquiries into the governance, planning, and long-term sustainability of megaprojects. The Study offers a strategic framework for policymakers, urban planners, and investors to make more informed, balanced decisions that align large-scale developments with broader economic and social priorities, mitigating risks associated with cost overruns, feasibility challenges, and socio-spatial disparities.